Parenting Patterns in Building Santriwati Discipline at Muhammadiyah An-Nur: Pola Pengasuhan dalam Membentuk Disiplin Santriwati di Muhammadiyah An-Nur - Jannah, Miftakhhul; Romadlon, Dzulfikar Akbar (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Islamic boarding schools play a significant role in shaping students’ character and discipline. Specific Background: Muhammadiyah An-Nur Sidoarjo is a relatively new boarding school that combines formal education and Islamic values. Gap: There is limited research focusing on parenting patterns and their role in forming discipline among female students (santriwati) in this context. Aim: This study aims to describe the parenting patterns, obstacles, and positive impacts in forming santriwati discipline. Method: A qualitative descriptive approach with a case study design was used. Data were collected through observation, interviews, and supporting documents. Results: Findings reveal that discipline formation is supported by regulations, positive activities, role models (ustadz/ustadzah), and structured education. Obstacles include wrong initial intentions, lack of knowledge practice, and poor adaptation. Novelty: This research highlights contextual parenting practices in a Muhammadiyah boarding school setting. Implications: The results can guide educators and administrators in designing more effective disciplinary programs and improving student adaptation. Highlights: Parenting patterns build santriwati discipline Regulations and role models are key factors Discipline impacts personal and social behavior Keyword: Parenting, Discipline, Islamic Boarding School, Santriwati, Qualitative Study